Author Correction: Self‑organization and culture of Mesenchymal Stem Cell spheroids in acoustic levitation - Nathan Jeger‑Madiot (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.